Trânsito em São Paulo: abordagem histórica e consequências sociais - Nogueira, Fernando Reis (2014)
This work is inserted into the debate about urban mobility, addressing more specifically urban mobility in the city of São Paulo. One of the largest and more populous cities in the world suffers from a continuing problem, the difficulty of urban mobility. São Paulo is facing a high level of dependence on individual transportation, deficiency in the implementation of a specific planning during and for the urban growth and lack of infrastructure of the public transportation. In this research, historically reconstruct the growth of the city of São Paulo, seeking to unfold the rise and the main causes of this urban problem: the mobility in megacities. The study also seeks to understand the various dimensions of urban planning or lack thereof, and the evolution forms of urban mobility throughout the century and contemporaneously